PENGOLAHAN VINASSE DARI AIR LIMBAH INDUSTRI ALKOHOL MENJADI BIOGAS MENGGUNAKAN BIOREAKTOR UASB - Soeprijanto Soeprijanto (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2010)
Distillery wastewater from ethanol fermentation has a high content of organic materials. Therefore, it can be used as raw materials for biogas production. The purpose of the experiment was to study the performance of Upflow Anaerobic Sludge Blanket (UASB) bioreactor to convert vinasse wastewater to biogas and other simple materials. A bioreactor was inoculated with 4 L sludge from a full-scale UASB bioreactor. The bioreactor was operated at a volume of 9 L. Vinasse was fed to the bottom of the bioreactor with a flow rate of 0.4 L/h using dosing pump. A variety of organic loading rates (OLR) applied were 5.49, 10.99, and 16.49 kg/m3.day respectively; and hydraulic retention time (HRT) of approximately 22 h. The results showed that the maximum COD removal was 61.59% and the maximum biogas volume was 4.59 L/day (3.28 L CH4/day) with OLR of 10.99 kg/m3.day. With OLR value of 5.49 kg/m3.day, a maximum CH4 content of 74.86%, CH4 yield of 0.11 m3 CH4/kg COD consumed, and a heating value of CH4 of 11,875 kcal/kg were achieved.